The impact of injuries study. multicentre study assessing physical, psychological, social and occupational functioning post injury - a protocol - Kendrick Denise; O'Brien Claire; Christie Nicola; Coupland Carol; Quinn Casey; Avis Mark; Barker Marcus; Barnes Jo; Coffey Frank; Joseph Stephen; Morris Andrew; Morriss Richard; et al. (BMC Public Health, 2011)
Abstract Background Large numbers of people are killed or severely injured following injuries each year and these injuries place a large burden on health care resources. The majority of the severely injured are not fully recovered 12-18 months later. Psychological disorders are common post injury and are associated with poorer functional and occupational outcomes. Much of this evidence comes from countries other than the UK, with differing health care and compensation systems. Early interventions can be effective in treating psychological morbidity, hence the scale and nature of the problem and its impact of functioning in the UK must be known before services can be designed to identify and manage psychological morbidity post injury. Methods/Design A longitudinal multi-centre study of 680 injured patients admitted to hospital in four areas across the UK: Nottingham, Leicester/Loughborough, Bristol and Surrey. A stratified sample of injuries will ensure a range of common and less common injuries will be included. Participants will complete a baseline questionnaire about their injury and pre-injury quality of life, and follow-up questionnaires 1, 2, 4, and 12 months post injury. Measures will include health and social care utilisation, perceptions of recovery, physical, psychological, social and occupational functioning and health-related quality of life. A nested qualitative study will explore the experiences of a sample of participants, their carers and service providers to inform service design. Discussion This study will quantify physical, psychological, social and occupational functioning and health and social care utilisation following a range of different types of injury and will assess the impact of psychological disorders on function and health service use. The findings will be used to guide the development of interventions to maximise recovery post injury.